The regional historiography in the system of russian university science - Petr A. Kuzminov; A. M. Kumykov; K. Ph. Dzamikhov (Высшее образование в России, 2022)
The problem of the development of Russian regional historiography, the role and place of the university science in its development are under discussion. The article reveals that modern Russian regional historiography requires systematic attention of Federal authorities for education and science.